Attitude of Tribal Farmers of Meghalaya towards ICT-Based Extension Services - Kharmudai, A.; Sumi, D.; S.P, Jyothi S. (Indian Journal of Hill Farming, 2018)
ICT is an important pillar that strengthens the extension activities in the current scenario and will bring new information services to rural farmers which will commence greater control than ever over current information channels. Access to such new information sources is a crucial requirement for the sustainable development of the farming systems. ICT when applied to the rural and agricultural conditions can improve the linkages between research sub-system and farmer sub-system. In this backdrop a study was conducted to observe if the Khasi tribal farmers have a favourable attitude towards the ICT - based extension services. Sixty respondents were randomly interviewed for the study. All of the farmers owned mobile phones and television or radio. The study revealed that majority of the farmers (81.67%) have a moderate favourable attitude towards the ICT-Based extension services whereas, 18.33 % of the respondents have a more favourable attitude. This means that there is a scope for higher usage of ICTs in disseminating the agriculture related information and the tribal farmers need to be aware of the advantages of using the information and communication technologies.